Recessional : the death of free speech and the cost of a free lunch - Mamet, David (Broadside Books, 2022)
Exposing how oppressive cultural codes--encapsulated in buzzwords such as inclusion, diversity, social justice, appropriation--are constricting the vibrant intellectual life of the world's freest country, a renowned author and playwright examines how politics and cultural attitudes about rebellion have shifted in the U.S. throughout history.